Gestão de ambiências bioecológicas (auto) formativas para o letramento racial: o que pensam e produzem os professores? - Rocha, Amanda Fontoura (2024)
This master's dissertation is part of the LP2 research line, entitled Pedagogical Management and Educational Contexts, of the Postgraduate Program in Public Policies and Educational Management of the Federal University of Santa Maria (UFSM). The continuing education of teachers should materialize in the school reality, with several ways of providing teachers with knowledge to develop content and pedagogical crafts that are significant for racial literacies. From this reflection, two questions generated the research: How have teachers of the Initial Years of Elementary Education (A.I.E.F.) prepared themselves, individually and as a group, to act in a qualified manner in the classroom, with ethnic-cultural-racial and racial literacy issues? [Research]; how have the A.I.E.F. teachers organized themselves to understand ethnic-cultural-racial and racial literacy issues to promote the movement of children through bioecological ambiences? [Product]. Thus, the general objectives were to investigate the individual and collective training needs of the A.I.E.F. teachers to work in the classroom with ethnic-cultural-racial and racial literacy issues; to collectively generate in bioecological (self) training ambiences bricolages proposed by the A.I.E.F. teachers on ethnic-cultural-racial issues and/or racial literacy. The specific objectives were: to map the individual and collective training needs of the A.I.E.F. teachers to promote bricolages with ethnic-cultural-racial and racial literacy issues; to ask the teachers for suggestions for the production of bioecological (self) training ambiences; to organize with the A.I.E.F. teachers the possibilities of constructing bricolages on ethnic-cultural-racial and racial literacy issues, materializing the pedagogical management of the bioecological (self) training ambiences; describe the product considering the author's DIY projects with the children and other elements that constituted the bioecological (self) formative ambiences with her fellow teachers. The mapping of the individual and collective training needs of the A.I.E.F. teachers to promote DIY projects with ethnic-cultural-racial issues and racial literacy was carried out through a Google Forms questionnaire and subsequent conversation circles. The teachers were asked for suggestions to produce the bioecological (self) formative ambiences, and an annual script to produce thematic pedagogical crafts was created, culminating in the organization of DIY projects on ethnic-cultural-racial issues and racial literacy. Thus, the pedagogical management model for the bioecological (self) formative ambiences was arrived at, involving teachers and children in the leading role of the product.